The Role of Artificial Intelligence in Transforming Entrepreneurs’ Strategic Decisions - fatma chikhaoui (PT. Literasi Teknologi Informatika, 2026)
In a globalized economic environment characterized by rapid transformation, intensified competition, and growing uncertainty, entrepreneurs face increasingly complex decision-making challenges. These conditions demand strategic choices that are rapid, precise, and grounded in reliable information. Digital transformation has profoundly disrupted traditional management practices, introducing a wide range of innovative technological tools designed to enhance organizational efficiency, responsiveness, and competitiveness. Among these technologies, Artificial Intelligence (AI) has emerged as a major driver of transformation, reshaping the way entrepreneurs collect, analyze, and interpret strategic information, identify emerging opportunities, and anticipate potential risks. This conceptual article is based on an integrative review of literature in entrepreneurship, strategic management, and information systems. It highlights the essential role of AI in entrepreneurial decision-making by drawing on existing literature in entrepreneurship, strategic management, and information systems. It emphasizes AI’s ability to support strategic choices through advanced data-processing techniques, predictive modeling, and automated analytics. The article adopts a structured conceptual approach, synthesizing different perspectives to clarify the mechanisms through which AI supports opportunity recognition, risk anticipation, and strategic decision-making under uncertainty. By enabling the extraction of relevant insights from large, diverse, and complex datasets, AI enhances forecasting accuracy, optimizes internal performance, and strengthens the agility of decision-making processes. The main contribution of this paper lies in proposing a conceptual framework and clarifying the theoretical mechanisms through which AI influences entrepreneurial decision-making, thereby offering a structured perspective on AI as a strategic enabler of more proactive, informed, and innovation-oriented decisions.